2020
DOI: 10.1242/jcs.245555
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid homeostatic control by TORC1 in Saccharomyces cerevisiae under high hydrostatic pressure

Abstract: Mechanical stresses including high hydrostatic pressure elicit diverse physiological effects on organisms. Gtr1/Gtr2 and Ego1/Ego3, central regulators of the TOR complex 1 (TORC1) nutrient signaling pathway, are required for the growth of Saccharomyces cerevisiae cells under high pressure. Here, we showed that a pressure of 25 MPa stimulates TORC1 to promote phosphorylation of Sch9, which depends on the EGO complex (EGOC) and Pib2. Incubation of cells at this pressure aberrantly increased the glutamine and ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Our previous studies have shown that defects in TRP1, TAT2 , TORC1-EGOC, or poorly characterized genes such as EHG1/MAY24 cause severe high-pressure sensitivity (Abe & Horikoshi, 2000, Abe & Minegishi, 2008, Kurosaka et al, 2019, Uemura et al, 2020). On the contrary, the defects in the CWI pathway and Fps1 shown in this study caused relatively mild sensitivity to high-pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have shown that defects in TRP1, TAT2 , TORC1-EGOC, or poorly characterized genes such as EHG1/MAY24 cause severe high-pressure sensitivity (Abe & Horikoshi, 2000, Abe & Minegishi, 2008, Kurosaka et al, 2019, Uemura et al, 2020). On the contrary, the defects in the CWI pathway and Fps1 shown in this study caused relatively mild sensitivity to high-pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of yeast cells at 25 MPa for 5 h resulted in the upregulation of the DAN/TIR family mannoprotein genes, which are known to be induced under hypoxic conditions and at low temperatures (Abe, 2007b). Target of rapamycin complex 1 (TORC1), an evolutionarily conserved serine/threonine kinase in eukaryotes, was activated by a pressure of 25 MPa (Uemura et al, 2020). We demonstrated that TORC1 plays a critical role in maintaining an appropriate glutamine level under high pressure by downregulating the de novo synthesis of glutamine (Uemura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the cells are starved or exposed to lethal stresses, TORC1 signaling is repressed, which leads to the downregulation of protein synthesis and effectively arrests cell growth [ 81 , 82 , 83 , 84 ]. A pressure of 25 MPa stimulated TORC1 to promote the phosphorylation of a downstream effector protein such as Sch9 [ 85 ]. This stimulation depends on the intracellular glutamine sensor protein, Pib2.…”
Section: High Pressure Activates a Nutrient Sensor Protein Kinase Complex Torc1mentioning
confidence: 99%
“…Mutants with deleted EGOC complex have an aberrant increase in glutamine levels. Therefore, the EGOC–TORC1 complex plays a critical role in maintaining an appropriate glutamine level under high pressure by downregulating the de novo synthesis of glutamine [ 85 ]. Although the mechanism by which high pressure causes glutamate accumulation is unclear, these findings provide a unique framework for understanding metabolic adaptation to high pressure.…”
Section: High Pressure Activates a Nutrient Sensor Protein Kinase Complex Torc1mentioning
confidence: 99%